2002
DOI: 10.1172/jci14873
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen alters thresholds for B cell apoptosis and activation

Abstract: Estrogen is thought to contribute to the increased frequency of autoimmune disorders occurring in females, but a molecular basis for its effects on autoimmunity remains to be elucidated. We have shown previously that estrogen leads to the survival and activation of autoreactive cells in the naive repertoire. To identify the molecular pathways involved in B cell tolerance, we sought to identify genes that are differentially regulated by estrogen in mouse B cells. Several genes involved in B cell activation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(40 citation statements)
references
References 54 publications
(22 reference statements)
2
36
0
Order By: Relevance
“…In a model of RA induced by transfer of hematopoietic stem cells from RA patients into immunodeficient mice, more B cells were retrieved from peripheral blood of female recipients compared with male recipients, indicating that sex-specific extrinsic microenvironmental factors rather than B-cell intrinsic factors contributed to the sex differences in the B-cell number 56 . Additionally, it was shown that estrogen increases the number of autoreactive B cells in the naive repertoire by protecting/increasing the survival of the immature B cells that would normally be deleted 57 . The greater proliferation of B cells in CII-stimulated dLN cell cultures from female compared with male rats is fully consistent with this finding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a model of RA induced by transfer of hematopoietic stem cells from RA patients into immunodeficient mice, more B cells were retrieved from peripheral blood of female recipients compared with male recipients, indicating that sex-specific extrinsic microenvironmental factors rather than B-cell intrinsic factors contributed to the sex differences in the B-cell number 56 . Additionally, it was shown that estrogen increases the number of autoreactive B cells in the naive repertoire by protecting/increasing the survival of the immature B cells that would normally be deleted 57 . The greater proliferation of B cells in CII-stimulated dLN cell cultures from female compared with male rats is fully consistent with this finding.…”
Section: Discussionmentioning
confidence: 99%
“…The greater proliferation of B cells in CII-stimulated dLN cell cultures from female compared with male rats is fully consistent with this finding. Furthermore, it was found that estrogen acting directly on B cells upregulates not only genes involved in B-cell survival but also in their activation 57 . These findings have been associated with an increased propensity towards the development of autoimmune diseases in female compared with male rats 57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects were observed in splenic B cells derived from ovariectomized mice (or not) administered with it. Interestingly, these results were reverted in mice treated with ICI 182,780 (128). Regarding the effects of GPR30 on B lymphocytes, some reports have mentioned that different chemokines can activate it, triggering different roles of B subsets such as migration, chemotaxis, proliferation, and apoptosis, among others.…”
Section: Estrogen Effects On Immune System Cellsmentioning
confidence: 99%
“…B lymphocytes are part of the adaptive immune system that is specialized in antibody production, which is part of humoral immunity (127). It has been described that B lymphocytes have the expression of both nuclear ERs in all B cell subsets (39, 128). In this sense, E2 has stimulatory effects on B-differentiated lymphocytes derived from human PBMCs.…”
Section: Estrogen Effects On Immune System Cellsmentioning
confidence: 99%